2004
DOI: 10.1523/jneurosci.2559-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of α-Synuclein in Presynaptic Dopamine Recruitment

Abstract: Real-time monitoring of stimulated dopamine release in mice with different ␣-synuclein expression was used to study the role of ␣-synuclein in presynaptic dopamine recruitment. Repeated electrical stimulations of ascending dopaminergic pathways decreased the capacity of the readily releasable pool (RRP) and temporarily increased its refilling rate, significantly slowing the rate of dopamine decline in mice with normally expressed ␣-synuclein. Mice with ␣-synuclein null mutation demonstrated a permanent increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
244
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(263 citation statements)
references
References 20 publications
16
244
0
3
Order By: Relevance
“…What is happening upon a-synuclein knockout? Here studies report decreased exocytosis [33,35,37,38], no change [36,39], or even increased exocytosis [40][41][42] (Table 2). However, these studies need to be interpreted with care because a-synuclein is not the only synuclein isoform, and loss of physiological function could possibly be compensated by b-or g-synuclein.…”
Section: Function Of A-synuclein On Synaptic Activity and Transmittermentioning
confidence: 65%
“…What is happening upon a-synuclein knockout? Here studies report decreased exocytosis [33,35,37,38], no change [36,39], or even increased exocytosis [40][41][42] (Table 2). However, these studies need to be interpreted with care because a-synuclein is not the only synuclein isoform, and loss of physiological function could possibly be compensated by b-or g-synuclein.…”
Section: Function Of A-synuclein On Synaptic Activity and Transmittermentioning
confidence: 65%
“…One theory suggested that -synuclein might be linked to PD via the regulation of dopamine (DA) homeostasis [19][20][21][22][23] . Several studies have proposed that -synuclein may be involved in regulating the biosynthesis, vesicles storage and release, as well as reuptake of DA [24][25][26][27][28][29][30][31] . In addition, -synuclein, as a chaperone, has been reported to interact with many other proteins, including 14-3-3, ERK1/2, parkin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of α-Syn resulted in reduction of dopamine release by interfering with a step after vesicle docking in exocytosis (27,28) or by inhibiting the reclustering of synaptic vesicles at the active zone after endocytosis (29). When the α-Syn level was reduced, the number of vesicles in the reserved pool decreased (30), but more vesicles were found in the readily releasable pool (31). In contrast, Südhof and coworkers (25) recently found that α-Syn promotes SNARE complex formation through its binding to a vesicular SNARE protein, synaptobrevin-2.…”
mentioning
confidence: 99%